Coda: The War of Poetry: Duncan’s Heresies - Michael Heller (Sillages Critiques)
This essay focuses on Duncan’s Tribunals: Passages 31-35, originally published as a separate chapbook in 1970, and the prose surrounding it, such as the earlier “The Sweetness and Greatness of Dante’s Divine Comedy” of 1964, as a central focus of the struggle of Duncan’s war with and for form, the site of risk, undoing and resolution. The “war” in which he is a protagonist most often wrestling with himself but also with the cultural and political environment in which he writes, is to liberate form – not to choose one form over another – but to bring form to possibility, to express form as the creative artist’s fulfillment of “the law that he creates,” to see poetry’s “every freedom,” as leading toward human liberation. Duncan often referred to himself as a “derivative poet.” This article discusses how such derivations were both an embrace and a strategy, each leading to a supersession of a poetics that enlarged the notion of poetry, selfhood and possibility.